ANALISIS HUBUNGAN GAYA KEPEMIMPINAN, PEREKRUTAN KARYAWAN DAN KETERLIBATAN KARYAWAN TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) DISTRIBUSI JAWA BARAT - Teguh Santoso (JURNAL LENTERA BISNIS, 2019)
This research was conducted to analyze the influences of leadership style , Employee Recruitment and employee involvement on employee employee performance of PT PLN (Persero) Distribusi Jawa Barat. The research methodology used is quantitative research by using a survey method that is intended to provide an explanation. The survey research is a study that takes a sample from a population and a questionnaire as a means of principal collecting. Two variables used are the independent variables and the dependent variable. Leadership style, Employee Recruitment and employee involvement as the independent variable and employee performance as the dependent variable. The research involves 72 employees as respondents, the data were analyzed with multiple linear regression model using SPSS. The results showed that leadership style, Employee Recruitment and employee involvement reac positively  and  significant to the job employees  satisfaction of PT PLN (Persero) Distribusi Jawa Barat. Keywords: Leadership Style, Employee Recruitment, Employee Involvement, Employee Performance